HUBUNGAN PEMBIAYAAN BANK UMUM SYARIAH DENGAN PERTUMBUHAN EKONOMI PROVINSI SUMATERA SELATAN - Humaidhi Semendawai (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2020)
The purpose of this study is to analyze the cointegration and the causal relationship between Islamic banks’ financing to economic growth in the province of South Sumatera.This research is used quarterly data from bi.go.id from 2010-2019. Research data were estimate by unit root test, Johansen cointegration test, VAR analize, impluse response, variance decompositionand Granger causality using Eviews program 6.The results of this research by Johansen cointegration test, it is found that there were no long-run equilibriun relationship between Islamic banks’ finance to economic growth in South Sumatera. The results of this research by Granger causality test, it is found that there were no causal relationship Islamic banks’ finance to economic growth in South Sumatera using critical value of 5 per cent, because of the probability values generated exceeds a critical value of 5 per cent or 0,05.